Teaching pain recognition through art: the Ramsay-Caravaggio sedation scale. - Poropat, Federico; Cozzi, Giorgio; Magnolato, Andrea; Monasta, Lorenzo; Borrometi, Fabio; Krauss, Baruch; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Clinical observation is a key component of medical ability, enabling immediate evaluation of the patient's emotional state and contributing to a clinical clue that leads to final decision making. In medical schools, the art of learning to look can be taught using medical humanities and especially visual arts. By presenting a Ramsay sedation score (RSS) integrated with Caravaggio's paintings during a procedural sedation conference for pediatric residents, we want to test the effectiveness of this approach to improve the quality of learning. METHODS: In this preliminary study, we presented videos showing sedated pediatric patients in the setting of a procedural sedation lesson to two randomized groups of residents, one attending a lesson on RSS explained through the masterpieces of Caravaggio, the other without artistic support. A week later we tested their learning with ten multi-choice questions focused on theoretical questions about sedation monitoring and ten more questions focused on recognizing the appropriate RSS viewing the videos. The primary outcome was the comparison of the total number of RSS layers properly recognized in both groups. We also evaluated the appreciation of the residents of the use of works of art integrated with the lesson. RESULTS: Eleven students were randomized to each group. Two residents in the standard lesson did not attend the test. The percentage of correct answers on the theoretical part was similar, 82% in the art group and 89% in the other (p > 0.05). No difference was found in the video recognition part of the RSS recognition test. Residents exposed to paintings shown great appreciation for the integration of the lesson with the Caravaggio's masterpieces. CONCLUSIONS: Adding artwork to a standard medical conference does not improve the performance of student tests, although this approach has been greatly appreciated by residents.
Keywords: Clinical Competence; Conscious Sedation; Deep Sedation; Education, Medical, Graduate; Female; Hospitals, University; Humans; Internship and Residency; Italy; Male; Medicine in the Arts; Monitoring, Physiologic; Pain Measurement; Paintings; Pediatrics; Video Recording